Sustainable development of Chinese higher education through comparison of higher education indices - Wu, Qiong; Borhan, Mohamad Termizi (Frontiers in Education, 2024)
The purpose of this paper is to focus on the comparative study of higher education indices in Mainland China and between the 31 administrative divisions of Mainland China in the international evaluation system. These indices comparisons include the comparison between six continents, and several key countries in the world, and the comparison between Chinese internal regions and Malaysian internal regions, which are both in Asia. The numbers and rankings of higher education institutes listed in QS World University Rankings (QS) from various countries and regions during the 13 years from 2010-2023 are the basis of corresponding higher education indices which were obtained through several calculation formulas. These indices are QS Higher Education Density Index (QSHEDI), QS Higher Education Quality Index (QSHEQI), QS Higher Education Composite Index (QSHEI), and Relative QS Higher Education Composite Index (RQSHEI) all reflect the index calculation results of the density, quality, and composite of higher education relative to the regional population. Based on the comparative analysis of the indices from multiple perspectives, this research found that there is a large gap between higher education in mainland China and other countries, and there is also a significant imbalance in the geographical distribution of higher education resources among provinces in mainland China based on the population proportion and economic impact. These problems will hurt the sustainable development of higher education in China. Therefore, paying more attention to the international evaluation system and recognition standards like the QS Rankings becomes necessary to guide the balanced development of higher education among provinces according to the population proportion. It is also important to improve the international influence of HEIs in mainland China according to internationally recognized requirements so that China's higher education can develop sustainably in the process of global internationalization.